2013
DOI: 10.4161/cc.25691
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymerases are error-prone at RecA-mediated recombination intermediates

Abstract: G enetic studies have suggested thatY-family translesion DNA polymerase IV (DinB) performs error-prone recombination-directed replication (RDR) under conditions of stress due to its ability to promote mutations during double-strand break (DSB) repair in growth-limited E. coli cells. In recent studies we have demonstrated that pol IV is preferentially recruited to D-loop recombination intermediates at stressinduced concentrations and is highly mutagenic during RDR in vitro. These findings verify longstanding ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Purified Pol IV in solution can load at a D loop HR-intermediate-like structure (Figure 1 c ), catalyze DNA synthesis, and produce errors such as those seen in HR-MBR (Figure 1 d – f ) (Pomerantz et al 2013). These data provide biochemical support for the HR-MBR mechanism.…”
Section: Mutagenic Break Repair In Escherichia Coli Models Cancer Promentioning
confidence: 99%
“…Purified Pol IV in solution can load at a D loop HR-intermediate-like structure (Figure 1 c ), catalyze DNA synthesis, and produce errors such as those seen in HR-MBR (Figure 1 d – f ) (Pomerantz et al 2013). These data provide biochemical support for the HR-MBR mechanism.…”
Section: Mutagenic Break Repair In Escherichia Coli Models Cancer Promentioning
confidence: 99%
“…Together, these results support the existence of a TLS-independent mutagenic pathway. Pomerantz et al suggested that Pol I can be highly error-prone at RecA-mediated D-loops produced by DSB repair (Pomerantz, Goodman, and O'Donnell 2013). Hence, it is likely that CIP, by generating DSB, can fuel the creation of these RecA-mediated D-loops and the subsequent Pol I mutagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these results support the existence of a TLSindependent mutagenic pathway. Pomerantz et al suggested that Pol I can be highly errorprone at RecAmediated Dloops produced by DSB repair(56). Hence, it is likely that…”
mentioning
confidence: 99%
“…These observations suggest that pol IV promotes the formation of DBSs due to the BER-mediated removal of closely spaced 8-oxo-dGTPs incorporated by pol IV (16). Other studies indicate that pol IV has a role in the repair of DSBs (20,21,30,31,2229): First, pol IV physically interacts with the RecA recombinase and RecA nucleoprotein filaments (RecA*); a key player in DSB repair (DSBR) (26, 32). This interaction might facilitate pol IV to function in strand exchange (33).…”
Section: Mainmentioning
confidence: 99%
“…Interestingly, the mutagenic potential of pol IV is modulated by UmuD and the recombinase RecA (26,2931). UmuD induces error-free synthesis of pol IV (26), promoting long-lived association of pol IV with the DNA (32).…”
Section: Mainmentioning
confidence: 99%